Peran Kepolisian Dalam Menangani Tindak Pidana Penegroyokan Oleh Geng Motor Di Kota Medan Sesuai Pasal 170 Ayat 1 Kitab Undang-Undang Hukum Pidana (Studi Kasus Polrestabes Medan) - Pasaribu, Joe Fernando; Marihot Simanjuntak; Togar Sahat Manaek Sijabat; Micael Jeriko Damanik (Universitas Sari Mutiara Indonesia, 2024)
This research discusses the role of the police in handling criminal acts of beatings by motorbike gangs in Medan City in accordance with Article 170 paragraph 1 of the Criminal Code. To achieve the research objectives, the author conducted interviews with the Medan Police. The research method used is empirical juridical research. The results of this research show that the factors causing the crime of beatings are family factors, age factors, education factors, and solidarity factors. The Medan Police have made efforts to deal with acts of beatings by motorbike gangs, namely anticipatory efforts, restraint efforts, and proactive efforts. However, there are obstacles in dealing with criminal acts of beatings by motorbike gangs, namely law enforcement that is not strict enough, inadequate infrastructure, the perpetrators are mostly still students, and lack of participation from the community.of quite diverse collections about various scientific fields.